A relational database within the Leg Club Network: an audit. Issue 2 (25th November 2020) - McIntyre, Neil; Galazka, Anna Milena; Lindsay, Ellie; Bawden, Robert; Renyi, Roland
Abstract: The growing prevalence of venous leg ulcers in an ageing population presents challenges for wound care and management. The Lindsay Leg Club model is an alternative approach to the management of leg health that can improve patient outcomes. This article reports on an audit of a relational database located within the Leg Club Network, containing records of more than 17 000 patients (known as members) who attended a Leg Club in a 5‐year period (2014‐2019). Overall, over 266 000 member leg assessments and treatments were entered into the database. The average nurse‐member attendance time was 28 min, with a skill mix of 23% senior nurses, 70% qualified and associate nurses, and 7% nurses in supervisory roles. Healing rates averaged 62% after 12 weeks. Recurrence rates were 20% after 12 weeks. Annual clinical and volunteer hours averaged 821 and 800 h, respectively. Staffing costs were £28 per wound treatment or leg assessment with a typical duration of 27 min; 71% of members were aged 70 to 94 years old, which indicates the need for a service that caters to the specific requirements of this age group. However, no data on psychosocial and well‐being outcomes were recorded. Their inclusion in further developments of this database is recommended.